The CpxA/CpxR two-component system mediates regulation of Actinobacillus pleuropneumoniae cold growth - Yao, Qing; Xie, Tingting; Fu, Yu; Wan, Jiajia; Zhang, Wendie; Gao, Xuejun; Huang, Jing; Sun, Diangang; Zhang, Fuxian; Bei, Weicheng; Lei, Liancheng; Liu, Feng (Frontiers in Microbiology, 2022)
To survive in various hostile environments, two-component system is an adaptive mechanism for diverse bacteria. Activity of the CpxA/CpxR two-component system contributes to coping with different stimuli, such as pH, osmotic and heat stress. However, the role of the CpxA/CpxR system in cold resistance is little-known. A. pleuropneumoniae is the aetiological agent of pig pleuropneumonia, which causes high economic losses in the swine industry globally. In this study, we showed that CpxA/CpxR was critical for A. pleuropneumoniae growth under cold stress. β-Galactosidase analysis showed that CpxA/CpxR positively regulated the predicted cold stress gene cspC. The mutant for cold stress gene cspC was impaired in the optimal growth of A. pleuropneumoniae under cold stress. Furthermore, electrophoretic mobility shift assays demonstrated that CpxR-P could directly regulate the transcription of the cold stress gene cspC. These results presented in this study illustrated that the CpxA/CpxR system plays an important role in cold resistance by upregulating expression of CspC. The data give new insights into how A. pleuropneumoniae survives in cold stress.